2015
DOI: 10.1590/1516-635x1704545-552
|View full text |Cite
|
Sign up to set email alerts
|

Serotypes of Salmonella in Broiler Carcasses Marketed at Ibague, Colombia.

Abstract: Salmonella enterica is a large group of Gram-negative bacteria responsible for a number of foodborne infections associated with the consumption of contaminated poultry products. The hygienic status of raw chicken meat marketed at Ibague, Tolima, Colombia, is currently unknown. To address this issue, a cross-sectional study was conducted to estimate the prevalence of Salmonella spp., in raw chicken marketed at different outlets in this city. Salmonella spp. was isolated by standard microbiological methods, foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
2
2

Year Published

2016
2016
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 41 publications
3
12
2
2
Order By: Relevance
“…On the other hand, this variant was the most prevalent in broiler flocks in Belgium (12.3%) and Germany (10.8%) [ 36 ]. However, the result of this study contrasts with the work done by Rodriguez et al [ 26 ], where at least 14 different serovars were isolated from broiler carcasses (47/270) marketed in the capital of Tolima region. As has been discussed in previous works, the results strengthen the hypothesis that contamination of broiler carcasses with a number of potentially pathogenic serovars of Salmonella might be occurring.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…On the other hand, this variant was the most prevalent in broiler flocks in Belgium (12.3%) and Germany (10.8%) [ 36 ]. However, the result of this study contrasts with the work done by Rodriguez et al [ 26 ], where at least 14 different serovars were isolated from broiler carcasses (47/270) marketed in the capital of Tolima region. As has been discussed in previous works, the results strengthen the hypothesis that contamination of broiler carcasses with a number of potentially pathogenic serovars of Salmonella might be occurring.…”
Section: Discussioncontrasting
confidence: 99%
“…Since the prevalence of Salmonella in broiler carcasses marketed in Ibague city was 17.4% in 2014 and S . Paratyphi B was the serotype most frequently (36.17%) [ 26 ] isolated, together the data suggest the dissemination of S . Paratyphi B from poultry farm to consumer.…”
Section: Discussionmentioning
confidence: 99%
“…The isolation rate was 10.0% from local chickens and 12.0% from broilers, suggesting there was no difference in the isolation rates from differentially sourced chickens in this study. Our findings were similar to the report of Rodriguez et al (2015) who reported a prevalence of 17.41% of Salmonella spp. in broilers at Ibague, Colombia, and of Al-Khayat & Khammas (2016) who reported a prevalence of 10.4% of Salmonella from layers and broilers in Baghdad.…”
Section: Discussionsupporting
confidence: 93%
“…The most common and clinically significant serovar containing the invA virulence gene that causes salmonellosis globally is S . Typhimurium and Salmonella enteritidis [ 19 ].…”
Section: Resultsmentioning
confidence: 99%